Global Identification of Anti-Melanoma Cellular Targets by Photochemically Induced Coupling of L-Shikonin Reactions on the Surface of Magnetic Particles - Min Li; Wenying Li; Fang Xu; Yiping Pu; Jianguang Li (Pharmaceutics)
Background: L-Shikonin, an active component of Arnebia euchroma (Royle) Johnst., has remarkable pharmacological effects, particularly in its anti-tumour activity. Nonetheless, the specific targets and mechanisms of action remain to be further explored. Methods: A novel Fe3O4@L-Shikonin was designed and synthesized in this study by linking Fe3O4 and L-Shikonin through benzophenone. Fe3O4@L-Shikonin was characterized using several techniques, including scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR), and drug removal methods, to determine the content of L-Shikonin on the surface of the magnetic particles. Target hooking technology was utilized to identify the target proteins of the compound in melanoma. The synthesized Fe3O4@L-Shikonin was co-incubated with A375 cell lysate, followed by the target proteins, which were purified by magnetic enrichment using magnetic microspheres and identified by high-resolution mass spectrometry. Results: AutoDock Vina software was employed for molecular docking analysis, where it was found that L-Shikonin targets RPN1, CPEB4, and HNRNPUL1 proteins. Subsequently, A375 cells were treated with L-Shikonin at different concentrations (2.5, 5.0, 10.0 μM) for 48 h, and the expressions of the three proteins were observed. The results showed a significant reduction in the relative expression of CPEB4 in the high-dose group compared to the control group (p < 0.01). Moreover, the relative expression of HNRNPUL1 was decreased in the medium- and high-dose groups (p < 0.05). Conclusions: This study initially revealed from the source that L-Shikonin may regulate melanoma-specific markers, melanosomes, tyrosine kinases related to abnormal tyrosine metabolism, and melanoma through multiple targets such as CPEB4 and HNRNPUL1. Proliferation and metastasis work together to exert an anti-melanoma mechanism, which provides a new idea for the follow-up study of the molecular pharmacological mechanism of the complex system of total naphthoquinones in Arnebia euchroma (Royle) Johns.